Accelerating the peroxidase-like activity of MoSe2 nanosheets at physiological pH by dextran modification. Issue 74 (13th August 2020) - Jiang, Gaoyan; Lin, Tianran; Qin, Yuxin; Zhang, Xuanhan; Hou, Li; Sun, Ying; Huang, Juanjuan; Liu, Shendong; Zhao, Shulin
Abstract : One-pot synthesis of dextran-modified MoSe2 nanosheets with peroxidase-like activity at physiological pH for bio-sensing. Abstract : Surface modification of MoSe2 via dextran during ultrasound exfoliation is demonstrated to be an efficient and easy strategy to accelerate the peroxidase-like catalytic activity of MoSe2 nanosheets at neutral pH. The enhancement of catalytic activity is owing to the rich negative charges of dextran on the dextran-modified MoSe2 nanosheets.